Post-Operative Superior Mesenteric Artery Syndrome Following Retroperitoneal Sarcoma Resection - Liam H. Wong; Thomas L. Sutton; Ryan G. Spurrier; Andrew F. Zigman; Skye C. Mayo (Clinics and Practice, 2020)
Superior mesenteric artery (SMA) syndrome is an uncommon phenomenon caused by the compression of the third portion of the duodenum between the aorta and the SMA. Here, we present a previously healthy 15-year-old male who presented with early satiety and 20 kg weight loss. Computed tomography (CT) demonstrated a massive retroperitoneal liposarcoma displacing the entire small intestine into the right upper quadrant. Following resection of the large mass, the patient was intolerant of oral intake despite evidence of bowel function. Abdominal CT revealed a narrowing of the duodenum at the location of the SMA. A nasojejunal feeding tube was placed past this area, and enteral nutrition was initiated before slowly resuming oral intake. Post-operative SMA syndrome is an uncommon complication but should be considered in patients intolerant of oral intake following resection of large abdominal tumors associated with extensive retroperitoneal fat loss, even in the absence of concomitant major visceral resection.